Rheological characterization of streptomyces roseosporus for the production of daptomycin - Chakravarty I.; Singh S.; Kundu S. (My University, 2025)
Daptomycin is a potential broad-spectrum anti-MRSA antibiotic produced by Streptomyces roseosporus. It has been a boon for patients with complicated skin and skin structure infections. There is a constant urge to enhance the yield of Daptomycin to reduce the cost of its industrial production. Daptomycin fermentation is a highly aerobic process, and the fermentation broth exhibits typical rheological properties, which peculiarly govern the production phenomenon. Being a secondary metabolite, Daptomycin is a non-growth associated product. Sufficient cell mass promises better production. The cell growth is particularly affected by stress conditions in the broth. In this study, the effects of stress conditions on broth characteristics were evaluated. Different rheological models were plotted and the Power law model was found to be best-fitted. The consistency index (K) and the flow behavior index (n) data were calculated. This study should contribute to predict and control the rheology of large-scale Daptomycin fermentation.